Physical inactivity and longer periods of sedentary behavior impact the quality of life of people living with HIV: a cross-sectional study - Lorhoâne Eduarda Simão de Morais; Giovana de Souza Gonçalves; Beatriz Toyama Watanabe; Daniela Jordana Santos da Silva; Alice Pereira Vieira; Marília Brasil Xavier; Luiz Fernando Gouvêa-e-Silva (Sport Sciences for Health, 2026)
Abstract Objective This study aimed to analyze the relationship between physical activity (PA) level, sedentary behavior (SB) duration, and the quality of life (QoL) among people living with HIV (PLWH). Methods In total, 183 PLHIV from a Reference Center in Santarém, Pará, Brazil, participated in this cross-sectional study. Information was collected on socioeconomic, clinical, QoL, PA, and SB variables. The data were analyzed using descriptive and inferential statistics, adopting p< 0.05. Results Participants had a mean age of 36.49±11.27 years, and most were male (58%). Physically active PLWH showed higher scores for their overall function ( p =0.002) and life satisfaction ( p =0.002) domains, compared with physically inactive individuals. Physical inactivity was associated with trust in the professional domain ( p= 0.036), while SB >4 h/day was negatively associated with overall function ( p= 0.003). Conclusion It is concluded that reducing SB and being physically active contribute to improving the QoL of PLHIV, particularly in relation to general function and life satisfaction.